From silos to synergy: a consortium approach to air pollution and public health in Abu Dhabi - Barrak Alahmad; Ernani F. Choma; Basem Al-Omari; Eman Alefishat; Abdu Adem; John S. Evans; Petros Koutrakis; Senthil Rajasekaran (BMC, 2024)
Abstract Financial resources alone cannot guarantee effective public health policy. In Abu Dhabi, massive economic growth in the desert climate resulted in concentrated urbanization and led to challenges in the regulation of air pollution. The Environment Agency in Abu Dhabi commissioned us to scope the regulatory challenges for air pollution. Part of this project relied on the participation and involvement of key stakeholders. We found three barriers: (1) limited appreciation of uncertainties in risk estimates and discussion on the importance of considering control costs and the societal trade-offs between health and wealth inherent in such decisions, (2) compartmentalization of efforts, and (3) challenges to decide how to prioritize risks in policy agendas. We propose a consortium-like approach that brings stakeholders together and places risk, uncertainty, and tradeoffs between health and wealth at the forefront of decision-making. Expected outcomes include improved collaboration and information sharing, strategic prioritization of emission controls, and a better understanding and consideration of uncertainty to guide future public health research.